“Shake ‘n Bake” Route to Functionalized Zr-UiO-66 Metal–Organic Frameworks - Matthew McPherson (Inorganic Chemistry, 2021)
We report a novel synthetic procedure for the high-yield synthesis of metal-organic frameworks (MOFs) with topology with a UiO-66-like structure starting from a range of commercial Zr precursors and various substituted dicarboxylic linkers. The syntheses are carried out by grinding in a ball mill the starting reagents, namely, Zr salts and the dicarboxylic linkers, in the presence of a small amount of acetic acid and water (1 mL total volume for 1 mmol of each reagent), followed by incubation at either room temperature or 120 °C. Such a simple "shake 'n bake" procedure, inspired by the solid-state reaction of inorganic materials, such as oxides, avoids the use of large amounts of solvents generally used for the syntheses of Zr-MOF. Acidity of the linkers and the amount of water are found to be crucial factors in affording materials of quality comparable to that of products obtained under solvo- or hydrothermal conditions.